(untitled) (Fiep Bulletin - online, 2013)
No countryin the world, in anyteam sportpresentsthe amountof winsthatholds theBrazilian volleyballon the international scene. These victoriesaccredittheBrazilian volleyballtitleof beingone of thebest in the world, considering the amount oftitles wonat the world championshipsin categoriesjuvenile, juvenile, adult, under-19andunder-21, men and womeninsuits. Resultsthatarealonecompelcheck whichenvironmentsare traversedto acquirethese achievements, as these victories, have astructuralapparatustowhich theyare achieved, particularlywith regardto themanagement of alltechnical and administrativeframeworknecessaryforsuch.Theacademicstudy investigatedtheroleand proceduresoftheBrazilian volleyballmanagersof 10of the twenty sevensportsfederationsthatexist in Brazil. The methodologyconsisted of aqualitative studyusing interviews, document analysis and content analysis.The resultsshow thatspecific training inphysical education andsports managementare not thebiggestbuoy tendersin effortssuccessful, consideringthat 90% of respondentshave nospecific trainingbut agreat experience ofadministration in generaladdingto thisexperience asathletemode.